Penerapan Metode Pembelajaran Berbasis Information and Communication Technology pada Mata Pelajaran Pekerjaan Dasar Elektromekanik - Roni Eka Rahmat; Hansi Effendi (Jurnal Pendidikan Teknik Elektro, 2020)
The role of the teacher as a learning center in transferring the learning material that is still using the lecture method and abstract will have an impact on the students' lack of activity in the teaching and learning process so that it causes to the student learning outcomes to be under of the minimum completeness criteria. It encourages the researcher to do research about the application of ICT-based learning methods on PDE subjects at SMK Muhammadiyah in Padang. This study used the pre-experimental method with the design of one group pretest-posttest and the subject used was class X TITLA as an experimental class. The data collection used the test instruments in the form of objective questions with the number of questions as many as 20 questions. The data were analyzed using classical completeness and effect size to see the magnitude of the application effect of ICT-based learning methods. Based on the result of the study, the average value of the pretest obtained was 58.83 and the average value of the posttest reached 85.17. The result showed that there was an increase in student learning outcomes after the implementation of ICT-based methods on PDE subjects in class X TITLA SMK Muhammadiyah Padang. The calculation of the data with the effect size was obtained 2.375 with the percentage of the classical completeness of learning was 90%. Thus, the application of the ICT-based learning method was effectively applied to the class X TITLA PDE subjects at SMK Muhammadiyah 1 Padang.